2021
DOI: 10.1155/2021/4159149
|View full text |Cite
|
Sign up to set email alerts
|

Interval Type-2 Fuzzy Standardized Cumulative Sum Control Charts in Production of Fertilizers

Abstract: Statistical process control is a method used for controlling processes in which causes of variations and correction actions can be observed. Control chart is one of the powerful tools of statistical process control that are used to control nonconforming products. Previous literature suggests that fuzzy charts are more sensitive than conventional control charts, and hence, they provide better quality and conformance of products. Nevertheless, some of the data used are more suitable to be presented in interval t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Previous research indicated that there are various kind of research that had been explored on interval type-2 fuzzy control charts other than interval type-2 fuzzy 𝑋 ̅ and R control charts. For instance, Mohd Razali et al (2021) conclude that the interval type-2 fuzzy Cumulative Sum (CUSUM) chart is more sensitive and accurate in monitoring the analysis by comparing the proposed method with the type-1 fuzzy CUSUM chart and conventional chart.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that there are various kind of research that had been explored on interval type-2 fuzzy control charts other than interval type-2 fuzzy 𝑋 ̅ and R control charts. For instance, Mohd Razali et al (2021) conclude that the interval type-2 fuzzy Cumulative Sum (CUSUM) chart is more sensitive and accurate in monitoring the analysis by comparing the proposed method with the type-1 fuzzy CUSUM chart and conventional chart.…”
Section: Introductionmentioning
confidence: 99%
“…The Anderson-Darling test was chosen over other similar statistical tests like a Kolmogorov-Smirnov test because it gives more weight to the tails of the distributions and has greater statistical power at small sample sizes while remaining flexible (Mohd Razali & Yap 2011). The data are standardized and compared to a reference distribution, 0, 1…”
Section: Appendix Statistical Tests Of Skewnessmentioning
confidence: 99%
“…Intervention analysis can be performed using the Cumulative Sum [CUSUM] method given in Hipel and McLeod [ 21 ] to determine the likely date/time of intervention in a given time series, or changes in environmental regime [ 22 ], if any. Razali, Abdullah [ 23 ] also used CUSUM methodology in examining conformance of the quality of the fertilizer production and even the method has been used in psychometric research to detect aberrant responses in a response sequence, e.g., test speediness, inattentiveness, or cheating [ 24 ]. On the whole, CUSUM is a well-established statistical process control method to detect changes in a sequence [ 24 ], hence has been used for determining the impact of intervention measures such as on road fatalities, if any.…”
Section: Methodsmentioning
confidence: 99%